HUBUNGAN SELF EFFICACY DENGAN KEPUASAN KERJA PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD CILEGON - Anisa (2023)
Nurses with a high level of self-efficacy can encourage good work results so that nurses' job satisfaction increases and positively affects the quality of services in the hospital. The purpose of the study was to determine the relationship between Self efficacy and nurse job satisfaction in providing nursing care in the inpatient room of RSUD Cilegon. The study design was quantitative-cross sectional with a sample of 112 nurses in the inpatient room of RSUD Cilegon and the method used was purposive sampling. Data analysis using the Chi-Square test with CI95% with a p value of 0.001 which means <0.05 so that it is concluded that there is a significant relationship between Self efficacy and nurse job satisfaction in providing nursing care in the inpatient room of Cilegon Hospital. For the head of the team, it is recommended to improve the task distribution system in the room so that nurses do not feel a high workload, for the head of the room, it is recommended that supervision be done better so that nurse motivation can increase so that job satisfaction arises. Keyword :, Job Satisfaction, Nurse, Inpatient, Self efficacy